PELUANG DAN TANTANGAN AGROINDUSTRI TEH RAKYAT DI JAWA BARAT - Lucyana Trimo; Syarif Hidayat (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Tea smallholder  plantations in Cianjur and Garut regencies have a very massive land function, resulting in the end of the shrinking of smallholder tea fields. The most urgent cause is the increasingly expensive wage of labor and the low price of tea tops received by farmers. This makes the farmers are no longer aroused to cultivate the plant properly. This is dependent on the provision of raw materials for the people's tea agro-industry, which eventually decreases the number of people's tea agro-industry. The research technique used is descriptive survey study. Research conducted in Garut and Cianjur regency, was chosen because included in the center of tea plantation in West Java Province. Sampling was done by simple random sampling method by 30 tea farmers in each area studied. Interviews were also conducted on: officials at government agencies, cooperatives, heads of tea agro-industry, farmer groups, selected purposively. The data and information owned are analyzed descriptively correlative and system thinking approach. Opportunities for the development of tea-tea agroindustry are still possible, in terms of: a) high demand for various processed products based on tea, b) to keep growing demand for tea in the world, c) smart, premium, and e) market support for countries with economic growth high. Challenges in the development of smallholder tea agroindustry can come from: a) human interests and capabilities, b) capital capital, c) land conversion, and d) innovation and creativity of processed products.